Strategi Pembelajaran Guru Pendidikan Agama Islam Dalam Menanggulangi Kenakalan Siswa Di SMA Negeri 1 Bandar Khalifah - Safriani, Indri; Kasran; Syahlan, Ali (STAI Tebing Tinggi Deli, 2024)
The purpose of this study was to determine how student delinquency is detrimental to the school and themselves, and how Islamic Religious Education teachers handle juvenile delinquency in SMA Negeri 1 Bandar Khalifah by focusing on the behavior and good morals of adolescents in overcoming juvenile delinquency. This study uses a descriptive qualitative approach by exploring data in the field. The researcher took the research location at SMA Negeri 1 Bandar Khalifah with three data collection methods used in this study, namely observation, interviews, and documentation. The results of the study showed that in SMA Negeri 1 Bandar Khalifah student delinquency was successfully overcome, the level of delinquency became lower indicating the success of overcoming delinquency in the school.